Rolling the Crypto Dice: The Interplay of Legal Environments, Market Uncertainty, and Gambling Attitudes on Users’ Behavioral Intentions - Ayman Abdalmajeed Alsmadi; Ahmed Shuhaiber; Khaled Saleh Al-Omoush (Human Behavior and Emerging Technologies)
The high volatility and inherent high-risk nature of cryptocurrency investments promote the study of the determinants of value perception and the various factors influencing individuals’ intentions regarding whether to adopt, abstain from, or continue their investments in these dynamic cryptocurrency markets. The main aim of this study is to examine the determinants of behavioral intention to continue using cryptocurrencies. In addition, it is aimed at exploring the effect of gambling attitudes on the perceived benefits and legal environment in the cryptocurrency context. An online questionnaire was developed in order to gather data from 258 respondents in the United Arab Emirates (UAE). The research model was assessed, and the hypotheses were tested using PLS-SEM. The outcomes of the PLS analysis revealed that gambling attitudes, perceived benefits, legal environment, and market uncertainty are significant determinants of behavioral intention to continue using cryptocurrencies. This study also revealed a significant effect of gambling attitudes and legal environment on the perceived benefits of cryptocurrencies. This study adds to the body of knowledge on cryptocurrency adoption by providing new insights into the factors that influence consumers’ continued investment. Furthermore, the study has crucial practical implications for cryptocurrency firms in promoting this financial technology to users by increasing policymakers’ understanding of how investors think and get inspired to continue investing in cryptocurrencies.